ANALISIS FAKTOR-FAKTOR KEUANGAN YANG MEMPENGARUHI FENOMENA UNDERPRICING PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2002-2010 - SOERYADJAYA WITJAKSONO, LYDIA (: 2303-1719)
Alternatively, one can do corporate funding for the development of his business is the issuance of shares. The share offer for the first time known as the Initial Public Offering (IPO). Share price at the time of the IPO are determined on the basis of an agreement between companies with underwriters. If the price at the time of IPO lower than the price that occurs on the first day on the stock exchange, then going underpricing. This research aims to examine the financial factors which include the size of the company, profitability, and financial leverage effect of the undepricing. Design research is quantitative and the research object is financial sector companies that are doing IPO at Indonesia stock exchange in 2002-2010. The samples used in research as much as 22 financial sector companies chosen by purposive sampling technique. Data sources obtained from the indonesia stock exchange. Data analysis is performed by multiple linear regression analysis. The results showed that the profitability negatively against underpricing. Meanwhile, size of the company and the financial leverage not influential against underpricing. It shows that profitability is essential information for investors in investing.